TECHNOCRATIC TOTALITARIANISM AS A RESPONSE TO THE CRISIS OF DEMOCRACY - LEWANDOWSKI Piotr (2023)
The article addresses the context of the transition and evolution of post-industrial societies, in which technocracy is emerging as an alternative to traditional democracy, better able to cope with the challenges of the present day. The purpose of this article is to explore how the level of meta-analysis contributes to assessing the effectiveness of technocracy compared to democracy by analyzing the nature of the crisis of democracy, the relationship between democracy and technocracy, the advantages of technocracy over democracy, the changes required by technocracy, and the impact of technocracy on the quality of social life and political power. The research problem, therefore, is to evaluate the effectiveness of democracy versus technocracy as a political system. This study conducts a holistic and comparative analysis of technocracy, democracy and their interrelationship in the context of contemporary political systems. Technocracy, based on the optimisation of processes and data, offers long-term strategies and instant responses to social and economic change. Despite this, critics point to its lack of moral and ideological underpinnings, leading to risks such as bureaucratisation and specialisation, limiting pluralism and individual freedom. An analysis of technocracy in the context of Neil Postman's concept shows the potential risk of losing social values, authority and individual freedom due to bureaucratisation. Technocracy, as a cult of science and technology, deifies science and reifies religion, leading to totalitarianism and dehumanisation, transforming individuals into means of production and consumption. This study emphasises that technocracy is not clearly positive or negative, but a complex phenomenon. On the one hand, it can bring efficiency and social development and, on the other, lead to a loss of fundamental values and freedom. The analysis of this issue takes into account different perspectives and contexts, allowing for a fuller understanding of its implications for contemporary societies. The study presented here is an in-depth analysis of technocracy, revealing its advantages, disadvantages and the risks it poses to society. It offers a comprehensive perspective on technocracy and its relationship with democracy, shedding light on the controversial debate on the future of governance in the post-industrial era.